2020
DOI: 10.1177/2055668320938588
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of motion detection with FMG and sEMG methods for assistive applications

Abstract: Introduction While surface-electromyography (sEMG) has been widely used in limb motion detection for the control of exoskeleton, there is an increasing interest to use forcemyography (FMG) method to detect motion. In this paper, we review the applications of two types of motion detection methods. Their performances were experimentally compared in day-to-day classification of forearm motions. The objective is to select a detection method suitable for motion assistance on a daily basis. Methods Comparisons of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The oldest research discussing FMG features is from 2017 [ 28 ], while most research has implemented FMG as raw signals for gesture recognition. The discussed features for force myography are primarily used in grasping detection, robot hand control, and gait analysis [ 28 , 29 , 30 , 31 , 32 ]. Many researchers have achieved hand gesture recognition based on various machine learning methods.…”
Section: Related Workmentioning
confidence: 99%
“…The oldest research discussing FMG features is from 2017 [ 28 ], while most research has implemented FMG as raw signals for gesture recognition. The discussed features for force myography are primarily used in grasping detection, robot hand control, and gait analysis [ 28 , 29 , 30 , 31 , 32 ]. Many researchers have achieved hand gesture recognition based on various machine learning methods.…”
Section: Related Workmentioning
confidence: 99%
“…A previous study showed the high similarity between the EMG-LE and the signal obtainable from a custom force sensor capable of detecting the mechanical activity of muscles (referred to as force-myography (FMG)) [24]. The advantages deriving from the use of FMG instead of EMG are various [25]: the problems related to EMG recording and its processing are avoided; the force sensor output can be used as is (no processing is required) and has already been successfully demonstrated for various applications (hand prosthesis control [26][27][28][29]; hand gesture recognition [30,31]; physiological parameters monitoring [32][33][34]); moreover, a very recent study suggests that force sensors seem to perform better than EMG in daily activities for exoskeleton controls [35].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to EMG, FMG is robust to electrical interference and sweating, whilst also being non-invasive and inexpensive [ 9 , 10 ]. In the work of Islam et al [ 11 ], the performance of motion detection with FMG and surface electromyography (sEMG) were compared in a daily scenario. They tested four different limb motions in five healthy male subjects.…”
Section: Introductionmentioning
confidence: 99%